2022
DOI: 10.1088/2051-672x/ac6f71
|View full text |Cite
|
Sign up to set email alerts
|

Sliding wear response of ultrasonic-assisted stir-squeeze cast Al-Zn(-Mg) alloy/ZrO2p composite: wear mechanism and subsurface deformation

Abstract: The character of hard ZrO2p in dry sliding wear of Al-Zn(-Mg) alloy was investigated in the cast and heat-treated conditions using pin-on-disc wear tester at fixed sliding speed (3.5 m/sec) and varying applied pressure (0.5-2.125 MPa), giving special accentuation on the response parameters such as seizure resistance, wear rate, and bulk temperature rise. Hardness behavior was also studied for the same concerned materials in accordance with ASTM standards. The composites exhibited enhanced hardness, wear and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…However, the material loss was less with increasing reinforcement TiB 2 concentration. Singh et al [125] examined the influence of varying applied pressure (0.5 to 2.125 MPa) dry sliding wear behavior of Al alloy composites reinforced with 2%-4% ZrO 2 particle and found that the wear rate initially increased with increasing applied pressure and eventually increased suddenly to a very high value when the materials got seized at higher pressures. The variation in the wear rate of materials in different conditions can be seen in figure 6.…”
Section: Influence Of Normal Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the material loss was less with increasing reinforcement TiB 2 concentration. Singh et al [125] examined the influence of varying applied pressure (0.5 to 2.125 MPa) dry sliding wear behavior of Al alloy composites reinforced with 2%-4% ZrO 2 particle and found that the wear rate initially increased with increasing applied pressure and eventually increased suddenly to a very high value when the materials got seized at higher pressures. The variation in the wear rate of materials in different conditions can be seen in figure 6.…”
Section: Influence Of Normal Loadmentioning
confidence: 99%
“…Because of mechanical joining/weld Figure 6. Wear rate variation in Al alloy and 2 and 4% ZrO 2 reinforced composite materials under heat-treated (HT) and as-cast (AC) conditions with respect to normal pressure (s: seizure) [125].…”
Section: Influence Of Sliding Distancementioning
confidence: 99%
“…Thus, there is a need to study the wear characterisation of AMCs under different conditions. Several investigations have focused on the abrasive wear and sliding behaviour of AMCs [33][34][35][36][37][38][39][40][41][42][43][44][45]3,7]. in contrast, very few studies have focused on the dry sliding wear behaviour of AMCs at high temperatures.…”
Section: Introductionmentioning
confidence: 99%